Mekanisme Rancangan Peraturan Perubahan Anggaran Pendapatan dan Belanja Daerah (APBD) (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
This study aims to find out about . What is the mechanism for drafting regulations on changes to the Regional Revenue and Expenditure Budget (APBD). What are the implications and legal impacts on regulatory mechanisms for amending the Regional Revenue and Expenditure Budget (APBD) which are not in accordance with statutory provisions. The method of data collection in this study was carried out by normative empirical, namely research that uses and processes primary data and side by side with secondary, empirical normative research is focused on the implementation of statutory (normative) legal provisions in action in every particular legal event that occurs in a society (empirical) related to the mechanism of Changes to the Regional Revenue and Expenditure Budget. The results of the study show that the Regional Revenue and Expenditure Budget, hereinafter abbreviated as APBD, is the regional government's annual financial plan that is discussed and agreed upon jointly by the local government and the Regional People's Representative Council (DPRD), and stipulated by regional regulations/Perda. The APBD budget year covers a period of one year, starting from January 1 to December 31. The Regional Revenue and Expenditure Budget consists of the Revenue Budget originating from Regional Original Revenue (PAD), which includes regional taxes, regional levies, regional wealth management results and the share of balancing funds, which includes Profit Sharing Funds, General Allocation Funds (DAU) and Funds Special Allocation. Also known as legitimate income such as grants or emergency funds. While the expenditure budget is the budget used for various purposes of carrying out government tasks in the region. The Regional Government submits a draft Regional Regulation concerning changes to the Regional Revenue and Expenditure Budget (APBD) for the current fiscal year to obtain approval from the Regional People's Representative Council (DPRD) before the end of the fiscal year. After obtaining approval from the Regional People's Legislative Council (DPRD) regarding the draft regional regulation regarding the Revised Regional Revenue and Expenditure Budget (APBD-P), then the process of evaluating and establishing the draft Regional Regulation concerning the Revised Regional Revenue and Expenditure Budget (APBD-P) and the draft Regional Head Regulations regarding the translation of the Amended Regional Revenue and Expenditure Budget (APBD-P) into Regional Regulations and Regional Head Regulations. There are two legal implications of the mechanism of the Amended Regional Revenue and Expenditure Budget (APBD-P) regulations which are not in accordance with statutory provisions. First, all processes of a series of changes that do not meet the normative requirements cannot be followed up directly. Second, administratively, all types of regional government work programs originate from the remaining budget from the previous year. (APBD-P) as the legal basis